The effect of PLGA nanoparticles on the osteogenic differentiation of hMSC - Dahlgren, Lukas (My University, 2017)
The polymer poly(lactic-co-glycolic acid) (PLGA) is both biocompatible and biodegradable and has therefore become one of the most frequently used polymers in the biomedical field. In this thesis, a literature study has been conducted on PLGA as a biomaterial. PLGA nanoparticles with a diameter of approximately 400 nm have been produced with the solvent evaporation method and the synthesis process has been analyzed and optimized. The synthesized nanoparticles have been used in in vitro studies on human mesenchymal stem cells, where their impact on cell viability and osteogenic differentiation has been investigated. For the nanoparticle synthesis, it was found that the concentration of stabilizer had the greatest impact on the result. Increased amount of stabilizer produced smaller particles. The in vitro studies were difficult to interpret, but implied that cell viability was negatively affected immediately after introduction of PLGA nanoparticles but that the cells quickly recovered. No difference in amount of expressed alkaline phosphatase, an osteogenic marker, could be observed between differentiated and non-differentiated samples. Deposits of extracellular calcium, another sign of osteogenesis, seemed to be enhanced by the particles upon visual inspection. However, this could not be proven quantitatively. These findings suggest that PLGA nanoparticles have an effect on the osteogenic differentiation of hMSCs, but the nature and extent of it needs to be investigated further.
Keywords: Nanovetenskap och nanoteknik; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Nanoteknik; Nanoscience & Nanotechnology; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Nano Technology